Textual Authority and Its Naturalization in Liang Shuming's Dong–Xi wenhua ji qi zhexue. Issue 1 (31st May 2017) - Major, Philippe
Abstract : This article discusses how Liang Shuming's Dong–Xi wenhua ji qi zhexue (Eastern and Western Cultures and Their Philosophies) adopted a genealogical mode of textual authorization which took shape in its depiction of Chinese history as a failure to live up to an ideal way of life imagined by Confucius. Implied in this discourse was the idea that Liang himself had been the first Confucian to understand what Confucius had truly meant. This genealogical discourse authorizing Liang and his text by linking them directly to Confucius was further strengthened by a rhetoric which naturalized the discourse passed down from Confucius to Liang, distinguishing it from other forms of discourse seen as artificial. Finally, the text's genealogical discourse also managed to incorporate the May Fourth critique of Confucianism by rejecting the historical manifestations of Confucianism before salvaging an ideal imagined by Confucius which was presented as uncontaminated by history and Confucianism's enmeshment in state power.